Cultural, morphological, pathogenic and biochemical variability in isolates of Pythium aphanidermatum, incitant of damping-off in bidi tobacco - K.R. JOSHI, D.L. YADAV* and (Indian Phytopathology, 2012)
Damping-off disease caused by Pythium aphanidermatum is a dreadful nursery disease which is resulting in huge loss in transplantable seedlings. In present study, six isolates of P. aphanidermatum were collected from three districts of bidi tobacco grown areas of middle Gujarat. All the six isolates (P1, P2, P3, P4, P5 and P6) produced white fluffy, dense mycelial growth within 24 hrs. and all the six isolates were apparently similar. The six isolates produced equal coenocytic mycelial diameter size (3 to 4Î¼m) with equal no. of branching. The oospores were produced after seven days in all the isolates which were of almost equal size. The isolates P1 and P2 were found highly virulent as compared to P3, P4, P5 and P6 isolates in pots as well as by hydroponic method. The hydroponic method was found relatively fast in producing the result as compared to soil inoculation method. Among the Polypeptide bands a highest band of molecular weight 90.4 KDa was observed in P1, P2 and P3 isolates. The bands of 22.91, 18.18 and 7.05 KDa were observed in all the isolates. Similarly significant variation was observed among the six isolates with respect to protein and esterase patterns. SDS-PAGE profiles of proteins of isolates indicated that an isolate P4 was unique in having one additional band with a molecular weight of 43.89 KDa. The dendrogram derived from similarity matrices using UPGMA software showed for SDSfinger printing profile revealed the presence of two clusters; cluster A and cluster B. P1, P2 and P3 constitute cluster A and P4, P5 and P6 formed cluster B.